1999
DOI: 10.1095/biolreprod60.5.1114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Major Histocompatibility Complex Class Ib Genes, Q7 and Q9, as the Ped Gene in the Mouse1

Abstract: The Ped (preimplantation embryonic development) gene influences the rate of preimplantation embryonic development and subsequent embryonic survival. The protein product of the Ped gene, the Qa-2 protein, is a major histocompatibility complex (MHC) class Ib protein. There are two alleles of the Ped gene, fast (Qa-2 [+]) and slow (Qa-2 [-]). Qa-2 is encoded by four very similar MHC class Ib genes: Q6, Q7, Q8, and Q9. Recent research in our laboratory has shown that the Ped phenotype is potentially encoded by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Indeed it modulates the expression of the mouse preimplantation embryonic development (Ped) genes (actually the Q7 and/or Q9 MHC class I genes), which govern the swiftness of preimplantation development (McElhinny et al, 1998;Wu et al, 1999). A similar mechanism seems to operate in humans, the nonclassical MHC class I gene, HLA-G, being a possible homologue of the mouse Ped gene (Jurisicova et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it modulates the expression of the mouse preimplantation embryonic development (Ped) genes (actually the Q7 and/or Q9 MHC class I genes), which govern the swiftness of preimplantation development (McElhinny et al, 1998;Wu et al, 1999). A similar mechanism seems to operate in humans, the nonclassical MHC class I gene, HLA-G, being a possible homologue of the mouse Ped gene (Jurisicova et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The Ped gene also has a role in blastocyst differentiation (7). The product of the Ped gene, the Qa-2 protein, is a mouse major histocompatibility complex (MHC) class Ib protein encoded by two almost identical genes (one nucleotide difference), Q7 and Q9 (6,8). However, other genes, in addition to the MHC encoded Ped, gene, play a role in the control of the rate of early preimplantation embryonic cleavage (9).…”
Section: Introductionmentioning
confidence: 99%
“…The Ped gene, a class Ib MHC component called the Qa-2 antigen (a glycosylphosphatidylinositol-linked cell surface protein encoded in the Q region of the mouse MHC), is associated with enhanced cleavage rate, larger blastocyst cell numbers, and greater midgestation survival (34,48,(53)(54)(55)(56). Previous reports concluded that the Ped phenotype is directed by the Q7 or Q9 genes, because Q6 and Q8 expression was undetected by RT-PCR (58,59). Our data indicate that the expression of H2-Q8 is low but detectable on arrays, leaving open the possibility that this gene may affect early cleavage rate.…”
Section: Discussionmentioning
confidence: 99%